Peranan Perbankan Bagi Pengembangan Lembaga Keuangan Mikro di Kota Medan - Aditya Pramudia; Cokie Ahmad Syawier (Ekonomi dan Keuangan, 2013)
The purpose of this study was to determine how the role of banks for the development of Microfinance Institutions in Medan and to determine whether financial aid (loans) from banks to Microfinance Institutions have significant effect on increasing profit Microfinance Institutions in Medan. The study was conducted at Microfinance Institute and Banking contained in Medan. The samples used were a total of 18 MFIs and banks of a number of banks and MFIs. Years of observation time series data is the year 2008 up to 2010. This study uses indicators Banking Disbursement as the independent variable (X) and Operating Profit Microfinance Institutions as the dependent variable (Y). The collected data were analyzed by the method of data analysis to prior classical assumption test before testing the hypothesis. Testing the hypothesis in this study using simple linear regression with partial t test with a significance level of 5%. The conclusion of this study is the role that banks have an insignificant role impact on the development of Microfinance Institutions in Medan. It is based on the number of average granting loans to Microfinance Institutions in Medan at 16.88%. Average number of operating profits of Microfinance Institutions just only 13.04%. The results of the t test showed a significance value of 0.715 whichis greater  than the value of alpha at 0,05. The results of the determinant test calculations are only 0.3% of distribution banking funds variable can explain operating  profit of Microfinance Institutions in Medan, while the remaining 99.7% is explained by other variables not included in this research model. Keywords : Role, Banking, MFI, Union, Medan